Hitler - Beneš - Tito Konflikt, Krieg und Völkermord in Ostmittel- und Südosteuropa, Band 1/2 - Suppan, Arnold (Verlag der Österreichischen Akademie der Wissenschaften, 2013)
Communities of conflict within Austrian-Hungary (especially in Bohemian and south Slav lands); the domestic and foreign policies of Czechoslovakia and Yugoslavia in the interwar-period; the Nazi policies of conquest and occupation in Bohemia, Moravia, Serbia, Bosnia-Herzegovina, and Slovenia, finalliy the issue of history and memory east and west of the Iron Curtan.